COMPARISON OF BREASTMILK PRODUCTION FROM MOTHERS OF PREMATURE AND MATURE BABIES DURING THE FIRST WEEK IN NICU SILOAM HOSPITALS KEBON JERUK - Dewanto, Naomi Esthernita F.; Napitupulu, Nancy (Fakultas Kedokteran Universitas Tarumanagara, 2021)
Background: The principal goal for infants especially preterm is the provision of the mother’s own milk (MOM), but on the other hand it is difficult to get MOM for preterm babies due to delayed of lactogenesis II and mother’s stress. Milk production and adequacy, for mothers of both healthy breastfeeding term infants and non-nursing preterm infants, have been shown to have a significant relationship with milk production 4-6 days after birth. This research aim to describe the comparison of milk production between mothers of premature and mature babies during the first week in NICU SHKJ. Methods: This is an observational descriptive with comparative study of mother’s milk production of preterm (<37 weeks) and term (>37 weeks) babies during the first week of life in NICU Siloam Hospitals Kebon Jeruk from 1st January until 31st December 2018. We documented the milk production from mothers breastmilk expression every 3-4 hours since 4-6 hours after delivery until day 7. Results: From 181 babies during 2018, we got 31 preterm and 77 term babies that we could documented from birth until day 7. The average breastmilk production of the preterm vs term mothers in each expression from day 1-7 were 0,81 vs 1,61 ml; 3 vs 3,65 ml; 6,66 vs 6,94 ml;21,5 vs 26,6 ml; 34,1 vs 46,4 ml; 45,92 vs 46 ml; 48,88 vs 50,4 ml/x expression.Conclusions: Expressing milk for a preterm or unwell baby requires commitment by the mother and effective support from staff. Commence breast milk expression as soon as possible after birth, at least within the first six hours, followed by frequent, regular and effective breast milk expression to stimulate adequate breast milk production may provide MOM for babies even for preterm babies in NICU with almost similar amount.